CARE PRINCIPAL IMPLEMENTATION IN REDUCING STUDENTS’ SPEAKING ANXIETY - Suparmi , Suparmi; Jafnihirda, Lika; Yunus, Yuliawati; Chang, Afnesha Noveriana (Jurnal Review Pendidikan dan Pengajaran, 2024)
The aim of this study was to identify how the implementation of Classroom Management concepts can reduce student’s speaking anxiety in vocational high school in Padang. The method used in this research is qualitative descriptive research that describe and explain a problem as it is. There are 9 English teachers as the subject of this study. This study used qualitative method by using questionnaire and observation as the instrument. The questionnaire of classroom management was developed based on the principle of classroom management such as Consistency, Awesomeness, Relationships, and Excellence (CARE). The result of this study where Consistency has 70% choose always, Awesomeness has 75% choose always, Relationship has 60% choose always score and Excellence has 50% choose always score. It means that almost all the English teachers always implementing the principle of classroom management during teaching and learning process. The data was support by the observation, the data showed that the teachers implemented the CARE principles and the students feel comfortable during learning process. By implementing the principle of classroom management, the students more confident to speak in front of the class.